Cassava starch grafted acrylamide hydrogel, its preparation method and application
Patent Information
- Application Number
- CN202611420315.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-09-14
- Publication Date
- 2026-10-20
AI Technical Summary
[0007]本发明的目的是提供一种木薯淀粉接枝丙烯酰胺水凝胶及其制备方法和应用,该水凝胶仅以丙烯酰胺为单一接枝单体,由木薯淀粉骨架与丙烯酰胺接枝支链通过交联形成三维网络结构,同时具有温度敏感性和pH敏感性双重响应特性,通过特定的原料配比和工艺参数使水凝胶的溶胀平衡比达到600%以上且可拉伸至原长度的5倍以上不断裂,以克服现有技术中木薯淀粉水凝胶缺乏双敏感特性、力学性能差的技术缺陷,并明确其在姜黄素药物缓释和重金属Cu2+吸附方面的具体应用方案和机理
1、本发明提供的木薯淀粉接枝丙烯酰胺水凝胶,仅以丙烯酰胺为单一接枝单体,区别于现有技术的丙烯酸与丙烯酰胺二元共聚体系;单一丙烯酰胺接枝体系在特定配比下形成的交联网络恰好落在亲水/疏水平衡的临界区间,使产物同时获得温度敏感性和pH敏感性双重响应特性,在35℃时溶胀平衡比达到最大值,在碱性条件下溶胀性能高于酸性条件。
Smart Images

Figure FT_1 
Figure FT_2 
Figure SMS_1
Abstract
Description
Technical Field
[0001] This invention relates to the field of functional polymer materials technology, specifically to a cassava starch-grafted acrylamide hydrogel, its preparation method, and its application. Background Technology
[0002] Hydrogels are a class of high molecular polymer materials with a three-dimensional network structure. Because their molecular chains contain a large number of hydrophilic groups, they can absorb tens or even hundreds of times more water than their own weight and have sensitive response characteristics to external stimuli (temperature, pH, ionic strength, etc.). They have attracted widespread attention in fields such as biomedicine and environmental remediation.
[0003] Starch is one of the most abundant natural polymers in nature, with advantages such as wide availability, low cost, biodegradability, and non-toxicity. Cassava starch, as a characteristic and advantageous resource of Guangxi, ranks first in the country in annual output, accounting for about 70% of the total national cassava starch output. It has the characteristics of low non-starch impurity content, high viscosity, low gelatinization temperature, and strong permeability. However, when natural cassava starch is used directly as a functional material, it has the following shortcomings: (1) it is insoluble in cold water and can only be dispersed after gelatinization; (2) it has poor mechanical strength and is difficult to form independently; (3) it lacks responsiveness to external stimuli.
[0004] There are already reports on technologies for modifying cassava starch to prepare hydrogels. For example, Chinese patent CN105693931A discloses a preparation process for a urea controlled-release carrier hydrogel, which uses cassava starch, acrylic acid, and acrylamide to synthesize a hydrogel via free radical initiation under the action of an initiator, for use in controlled-release fertilizers. Chinese patent CN105769748A discloses a cassava starch hydrogel mask matrix for *Nostoc commune* extract, which uses cassava starch gelatinized and modified with acrylic acid as a crosslinking agent to prepare a hydrogel for use in the cosmetics field. Existing research also shows that hydrogel materials with high water absorption ratios can be prepared using cassava starch as a raw material and acrylamide as a monomer.
[0005] However, existing technologies still have the following shortcomings: First, they lack dual temperature / pH sensitivity. The cassava starch hydrogels prepared by the aforementioned existing technologies are mainly designed to improve water absorption, without considering the dual response characteristics of temperature and pH sensitivity. Smart hydrogels that can simultaneously sense changes in temperature and pH and respond in volume have important application value in areas such as targeted drug release, but existing cassava starch-based hydrogels have not yet achieved this function. Second, their mechanical properties are insufficient. Traditional chemically cross-linked hydrogels are easily broken under small external forces, making it difficult to meet the mechanical strength requirements for use as drug carriers or adsorbent materials. Third, research on drug loading and sustained-release performance is lacking. Existing cassava starch hydrogel technologies focus more on preparation methods and water absorption, lacking systematic research on their drug loading behavior and sustained-release effects when used as drug carriers to load specific drug models. Fourth, research on heavy metal adsorption mechanisms is insufficient. Existing research on the adsorption of heavy metals by cassava starch hydrogels is mostly limited to single-factor investigations, lacking complete data support from adsorption kinetics, isothermal adsorption models, and thermodynamic parameters, resulting in an unclear adsorption mechanism.
[0006] Therefore, to address the aforementioned problems, this invention provides a cassava starch-grafted acrylamide hydrogel, its preparation method, and its applications. This solves the technical problems of existing cassava starch-based hydrogels, such as lack of dual temperature / pH sensitivity, poor mechanical properties, and inability to simultaneously achieve high swelling capacity and high mechanical strength. Furthermore, it clarifies its applications in the sustained release of curcumin and the treatment of heavy metal Cu. 2+ Specific applications in adsorption. Summary of the Invention
[0007] The purpose of this invention is to provide a cassava starch-grafted acrylamide hydrogel, its preparation method, and its applications. This hydrogel uses acrylamide as the sole graft monomer, forming a three-dimensional network structure through cross-linking of the cassava starch backbone and acrylamide grafted side chains. It exhibits dual-response characteristics of temperature and pH sensitivity. Through specific raw material ratios and process parameters, the hydrogel achieves a swelling equilibrium ratio exceeding 600% and can be stretched to more than five times its original length without breaking. This overcomes the technical shortcomings of existing cassava starch hydrogels, such as lack of dual-sensitivity properties and poor mechanical properties. Furthermore, it clarifies its applications in the sustained release of curcumin and the treatment of heavy metal Cu. 2+ Specific application schemes and mechanisms of adsorption.
[0008] The objective of this invention is achieved through the following technical solution: This invention provides a cassava starch-grafted acrylamide hydrogel. This hydrogel uses acrylamide as the sole graft monomer, forming a three-dimensional network structure through N,N-methylenebisacrylamide crosslinking between the cassava starch backbone and acrylamide grafted side chains. The hydrogel exhibits both temperature and pH sensitivity, reaching its maximum swelling equilibrium ratio at 35°C, and its swelling performance is higher under alkaline conditions than under acidic conditions. The swelling equilibrium ratio of this hydrogel is over 600%. After swelling equilibrium, the hydrogel can be stretched to more than five times its original length without breaking, rapidly rebounds to its original shape after compression, and remains intact when knotted. The infrared spectrum of this hydrogel is at 1678 cm⁻¹. -1 The hydrogel exhibits a characteristic absorption peak of CN amide and has a three-dimensional interconnected porous structure with a relative crystallinity of 18.32%.
[0009] Compared to existing technologies using binary copolymers of acrylic acid and acrylamide, this invention employs a single acrylamide grafting system. This avoids the disruption of the hydrophilic / hydrophobic balance in the network structure caused by the introduction of acrylic acid, achieving a critical equilibrium between crosslinking points and the network structure. This results in dual-response characteristics of both temperature and pH sensitivity. No existing technologies have reported dual-sensitivity properties in single acrylamide-grafted cassava starch hydrogels, and this effect is unpredictable. This hydrogel exhibits a sensitive volume response to changes in external temperature and pH, making it suitable for use as a smart drug release carrier. The hydrogel's swelling equilibrium ratio exceeds 600%, ensuring sufficient internal space for drug molecule loading and metal ion diffusion when used as a drug carrier and adsorbent. After swelling equilibrium, the hydrogel can be stretched to more than five times its original length without breaking, rapidly rebounds to its original shape after compression, and remains intact when knotted. These mechanical properties ensure that it can withstand external forces without fragmentation when implanted in vivo as a drug carrier or placed in water as an adsorbent, extending the material's lifespan. The hydrogel was characterized by infrared spectroscopy, scanning electron microscopy, and X-ray diffraction at a depth of 1678 cm⁻¹. -1 The presence of CN amide characteristic absorption peaks indicates that acrylamide has been successfully grafted onto the starch backbone; the three-dimensional interconnected porous structure provides ample physical space and diffusion channels for drug loading and ion adsorption; the relative crystallinity is 18.32%, which is significantly lower than the 31.67% crystallinity of the original cassava starch, and the increase in amorphous regions improves the material's permeability and swelling properties.
[0010] Preferably, the hydrogel reaches swelling equilibrium in distilled water within 3 hours. The swelling rate is an important indicator for evaluating the water absorption performance of a hydrogel; a faster swelling rate is beneficial for quickly reaching the usable state in practical applications and shortening the waiting time.
[0011] Preferably, the hydrogel has a curcumin loading capacity of 100 mg / g, and the curcumin-loaded hydrogel releases the curcumin at 37°C in phosphate buffer solution at pH 7.4, with a cumulative release rate of 80% over 72 hours. Curcumin is a natural drug with various pharmacological activities such as anti-inflammatory, antioxidant, and antitumor effects; however, its low water solubility, poor stability, and rapid metabolism limit its clinical application. The high curcumin loading capacity and sustained release capability of the hydrogel of this invention provide an effective carrier solution for addressing the problem of low curcumin bioavailability.
[0012] Preferably, the hydrogel is effective against Cu 2+ The equilibrium adsorption capacity was 10.39–18.39 mg / g. This adsorption capacity data provides a quantitative basis for the application of hydrogels as heavy metal adsorbent materials.
[0013] The present invention also provides a method for preparing the above-mentioned cassava starch grafted acrylamide hydrogel, comprising the following steps: (1) Add 1 part by weight of cassava starch to 100 parts by weight of distilled water, heat and stir in a water bath at 70~80℃ for 25~35 minutes to completely gelatinize the cassava starch and obtain starch gelatinized liquid; (2) Add 5 parts by weight of acrylamide monomer to the starch gelatinization liquid and stir at 70~80℃ for 15~25 minutes to make the acrylamide monomer and gelatinized starch evenly mixed; (3) Add 0.06 parts by weight of N,N-methylenebisacrylamide crosslinking agent and 5 parts by weight of distilled water to the mixture obtained in step (2) for dilution; (4) Dissolve 0.03 parts by weight of ammonium persulfate initiator in 5 parts by weight of distilled water, add it to the reaction system obtained in step (3), and continue stirring at 70~80℃ for 8~12 minutes to initiate graft copolymerization and crosslinking reaction; (5) After the reaction is completed, the gel is placed in a water bath at 70-80°C for 8-15 minutes to form a uniform gel. The gel is then poured into anhydrous ethanol and soaked for 1-3 minutes. After pouring out the ethanol, fresh anhydrous ethanol is added and the gel is soaked for 22-26 hours to complete the dehydration. The dehydrated gel is then dried in an oven at 45-55°C for 22-26 hours to obtain the cassava starch grafted acrylamide hydrogel.
[0014] Preferably, in step (1), the purpose of the gelatinization process is to disrupt the crystalline structure of starch granules, allowing the starch molecular chains to fully extend and expose more hydroxyl active sites, thus creating conditions for subsequent graft copolymerization reactions. This invention has determined gelatinization conditions of 70-80℃ and 25-35 minutes through numerous experiments. Too low a gelatinization temperature or too short a time will result in incomplete gelatinization and starch granule residue; too high a gelatinization temperature or too long a time may lead to starch molecular chain degradation, affecting the performance of the final product.
[0015] Preferably, in step (2), acrylamide is the single graft monomer used in this invention. Its molecular structure contains carbon-carbon double bonds and amide groups. The double bonds can be opened under the action of an initiator to participate in the polymerization reaction, while the amide groups provide hydrophilicity and responsiveness to the hydrogel. This invention uses a single acrylamide grafting system, which differs from the existing acrylic acid and acrylamide binary copolymer system, thus avoiding the disruption of the critical equilibrium of the network structure caused by the introduction of acrylic acid. The inventors unexpectedly discovered that, under a specific ratio, the crosslinked network formed by the single acrylamide grafting system falls precisely within the critical range of hydrophilic / hydrophobic equilibrium, thereby enabling the product to simultaneously acquire temperature sensitivity and pH sensitivity. This effect has not been reported in the prior art and is unpredictable.
[0016] Preferably, in step (3), the crosslinking agent connects linear polymer chains through chemical bonds to form a three-dimensional network structure, giving the hydrogel the property of swelling without dissolving. The amount of crosslinking agent is one of the key factors affecting the performance of the hydrogel: if the amount of crosslinking agent is too small, the crosslinking density is insufficient, the gel strength is insufficient, and it is easy to break after swelling; if the amount of crosslinking agent is too large, the number of crosslinking points increases, the crosslinking spacing becomes smaller, the network structure is too dense, the free space is reduced, and water molecules have difficulty entering, resulting in a decrease in swelling performance. This invention has determined the amount of crosslinking agent to be 0.06 parts by mass through a large number of experiments. At this amount, the crosslinking density is moderate, and the free volume of the network structure just meets the needs of water molecule entry and polymer chain segment movement.
[0017] Preferably, in step (4), the initiator decomposes to generate free radicals, which attack the hydroxyl groups on the starch molecular chain and the carbon-carbon double bonds of acrylamide, initiating a graft copolymerization reaction. The amount of initiator also affects the product performance: if there is too little initiator, the number of free radicals generated is insufficient, the grafting rate is low, and the reaction is incomplete; if there is too much initiator, the resulting molecular chains are short and numerous, the crosslinking density increases, and excessive initiator may lead to free radical degradation. This invention has determined the amount of initiator to be 0.03 parts by mass through a large number of experiments.
[0018] Preferably, in step (5), the purpose of ethanol soaking for dehydration is to remove water from the hydrogel, while simultaneously fixing the gel network structure through solvent replacement. The secondary alcohol replacement ensures sufficient dehydration and avoids the collapse of the network structure during drying due to residual moisture. Low-temperature drying (45~55℃) ensures both dehydration efficiency and avoids damage to the polymer chain structure caused by high temperatures.
[0019] Preferably, the gelatinization temperature in step (1) is 75°C and the gelatinization time is 30 minutes; the stirring temperature in step (2) is 75°C and the stirring time is 20 minutes; and the stirring temperature in step (4) is 75°C and the stirring time is 10 minutes. The above parameters were determined based on a large number of orthogonal experimental results, under which the swelling equilibrium ratio of the hydrogel reaches its highest value.
[0020] Preferably, the drying temperature in step (5) is 50°C, the drying time is 24 hours, and the anhydrous ethanol soaking time is 2 minutes and 24 hours. These drying conditions ensure that the hydrogel is fully dried to a constant weight while avoiding damage to the product structure caused by high temperature.
[0021] This invention also provides the application of the above-mentioned cassava starch-grafted acrylamide hydrogel as a sustained-release carrier for curcumin. The hydrogel is loaded with curcumin using an adsorption-based drug loading method. The loading conditions are: adsorption time 0.5 hours, ethanol concentration 20%, temperature 35°C, initial curcumin concentration 100 μg / mL, and the hydrogel's curcumin loading capacity reaches 100 mg / g. The curcumin-loaded hydrogel releases curcumin in phosphate buffer (pH 7.4) at 37°C, with a cumulative release rate of 80% over 72 hours. The curcumin release process is divided into a burst release phase (0-2 hours), a slow release phase (2-48 hours), and a sustained-release phase (48-72 hours). Comparative pure curcumin is completely released within 8 hours under the same conditions, with a release rate exceeding 99%.
[0022] The adsorption-based drug loading method is simple to operate and operates under mild conditions, requiring no additional chemical reagents and avoiding chemical changes in the drug during loading. Curcumin is poorly soluble in water and requires the addition of ethanol as a solubilizer; however, excessively high ethanol concentrations can cause the hydrogel to dehydrate and shrink, reducing the drug loading capacity. This invention experimentally determined that a 20% ethanol concentration is the optimal value for balancing drug solubility and hydrogel swelling. Adsorption equilibrium was reached within 0.5 hours, indicating that the hydrogel has a rapid adsorption rate for curcumin, which can shorten the production cycle.
[0023] The comparative experimental data show that the hydrogel of this invention has a significant sustained-release effect on curcumin—pure curcumin is completely released in 8 hours, while the sustained-release time of curcumin loaded in the hydrogel is extended to 72 hours, an extension of approximately 9 times. The burst release phase (0-2 hours) releases the drug adsorbed on the hydrogel surface, which is beneficial for quickly achieving an effective blood drug concentration at the initial stage of administration; the slow release phase (2-48 hours) achieves continuous and stable drug release, avoiding drastic fluctuations in blood drug concentration; and the equilibrium sustained-release phase (48-72 hours) further extends the duration of drug action. Compared with existing curcumin carriers, the hydrogel of this invention has significant advantages in both drug loading capacity and sustained-release duration. This sustained-release effect stems from the physical encapsulation of drug molecules by the three-dimensional network structure of the hydrogel—drug molecules are encapsulated by the network structure, extending their diffusion path from the inside of the gel to the outside, requiring them to overcome the resistance of the network segments to be released, thus achieving sustained release.
[0024] This invention also provides the above-mentioned cassava starch-grafted acrylamide hydrogel as a heavy metal Cu. 2+ Application of adsorbent materials. Adsorption conditions: per 50 mL Cu2+ The solution used 2.5 g of the hydrogel, the solution pH was neutral, the temperature was 35°C, and Cu... 2+ The initial concentration was 50 mg / L, and the adsorption time was 24 hours; the hydrogel was effective against Cu. 2+ The adsorption process conforms to a pseudo-second-order kinetic model, with a correlation coefficient R. 2 >0.999; the adsorption process conforms to the Freundlich isothermal adsorption model, with 1 / n values between 0.268 and 0.429; the adsorption thermodynamic parameters are ∆G<0, ∆H=18.926kJ / mol, and ∆S=73.627J / (mol·K), and the adsorption is a spontaneous endothermic process.
[0025] Under neutral pH conditions, the amino and carboxyl groups in the hydrogel exist in deprotonated forms (-NH2, -COO⁻), which can effectively capture Cu through coordination and electrostatic adsorption. 2+ Under acidic conditions, these groups are protonated (-NH3). + Cu(OH) chelation ability is weakened; Cu under alkaline conditions 2+ It is easily hydrolyzed to form a precipitate, which interferes with adsorption. The dosage of 2.5 g / 50 ml determined in this invention ensures a high adsorption rate while also taking into account the economy of the material.
[0026] The correlation coefficient R of the quasi-second-order dynamic model 2 The theoretical equilibrium adsorption capacity is >0.999, which is in high agreement with the experimental value, indicating that the adsorption is mainly chemisorption, and the adsorption rate is controlled by electron sharing or electron transfer between the adsorption site and the metal ion. The Freundlich isotherm adsorption model has a better fit than the Langmuir and Tempkin models, with 1 / n values between 0.268 and 0.429 (less than 1), indicating that the adsorption is multilayer adsorption and is easy to carry out. Among the adsorption thermodynamic parameters, ∆G < 0 indicates that the adsorption process can proceed spontaneously, and the absolute value of ∆G increases with increasing temperature, indicating that heating is beneficial to adsorption; ∆H = 18.926 kJ / mol > 0 indicates that the adsorption is an endothermic process, and increasing the temperature can increase the adsorption capacity; ∆S = 73.627 J / (mol·K) > 0 indicates that the adsorption process is mainly entropy-driven, that is, the disorder of the solid-liquid interface increases during the adsorption process. The complete data of the above kinetics, isotherms and thermodynamic parameters are applicable to the adsorption of Cu by cassava starch hydrogel. 2+ No systematic reports have been found in this study, which provides sufficient theoretical basis for the practical application of the hydrogel of this invention in the field of copper-containing wastewater treatment.
[0027] Due to the application of the above technical solution, the present invention has the following beneficial effects compared with the prior art: 1. The cassava starch grafted acrylamide hydrogel provided by the present invention uses acrylamide as the only grafting monomer, which is different from the existing acrylic acid and acrylamide binary copolymer system. The crosslinking network formed by the single acrylamide grafting system under a specific ratio falls exactly in the critical range of hydrophilic / hydrophobic balance, so that the product simultaneously obtains dual response characteristics of temperature sensitivity and pH sensitivity. The swelling balance ratio reaches its maximum value at 35°C, and the swelling performance under alkaline conditions is higher than that under acidic conditions.
[0028] 2. The hydrogel of this invention achieves a synergistic breakthrough in both high mechanical strength and high swelling performance: the swelling balance ratio reaches over 600%, and after swelling, it can be stretched to more than 5 times its original length without breaking, and it rebounds rapidly when compressed and remains intact when knotted; this synergistic effect stems from the unique network structure formed by the single acrylamide grafting system at the critical crosslinking density—the spacing between crosslinking points precisely allows the polymer chain segments to undergo reversible slippage under stress to impart mechanical strength, while retaining sufficient free volume for water to enter and exit to impart high swelling and responsiveness.
[0029] 3. The preparation method of this invention is simple and mild. The optimal ratio (cassava starch:acrylamide = 1:5, crosslinking agent 0.06 parts, initiator 0.03 parts) and process parameter range were determined through systematic investigation. The parameters of each step are clear and easy to scale up for production.
[0030] 4. The hydrogel of this invention serves as a sustained-release carrier for curcumin, with a drug loading capacity of 100 mg / g and a cumulative drug release rate of 80% over 72 hours, while pure curcumin is completely released in 8 hours. The sustained-release time is extended by about 9 times, resulting in a significant sustained-release effect.
[0031] 5. The hydrogel of this invention is used as a heavy metal Cu. 2+ The adsorption material exhibits adsorption that conforms to a pseudo-second-order kinetic model (R0). 2 The results, along with the Freundlich isotherm adsorption model (1 / n = 0.268~0.429) and thermodynamic parameters ∆G < 0, ∆H = 18.926 kJ / mol, and ∆S = 73.627 J / (mol·K), confirm that adsorption is a spontaneous endothermic process, providing a complete theoretical basis for the treatment of copper-containing wastewater. Attached Figure Description
[0032] To more clearly illustrate the specific embodiments of the present invention or the technical solutions in the prior art, the drawings used in the description of the specific embodiments or the prior art will be briefly introduced below. Obviously, some of the drawings in the following description are some embodiments of the present invention. For those skilled in the art, other drawings can be made based on these drawings without creative effort.
[0033] Figure 1This is a scanning electron microscope (SEM) image of the cassava starch grafted with acrylamide hydrogel in Example 1 of the present invention; Figure 2 This is a comparison of the appearance of the cassava starch grafted with acrylamide hydrogel before and after swelling in Example 1 of the present invention (left: before swelling; right: after swelling). Detailed Implementation
[0034] To provide a clearer understanding of the technical features, objectives, and effects of this invention, specific implementation schemes are now described in detail.
[0035] The present invention will be further described below with reference to embodiments, but the present invention is not limited to the following embodiments. The implementation conditions used in the embodiments can be further adjusted according to different requirements of specific use, and the implementation conditions not specified are conventional conditions in the industry. The technical features involved in the various embodiments of the present invention can be combined with each other as long as they do not conflict with each other.
[0036] Example 1 See appendix Figure 1 and appendix Figure 2 This embodiment provides a cassava starch-grafted acrylamide hydrogel and its preparation method, including the following steps: (1) Add 1g of cassava starch to 100mL of distilled water, heat and stir in a water bath at 75℃ for 30 minutes to completely gelatinize the cassava starch and obtain starch gelatinized liquid; (2) Add 5g of acrylamide monomer to the starch gelatinization liquid and stir at 75°C for 20 minutes to make the acrylamide monomer and gelatinized starch evenly mixed; (3) Add 0.06g of N,N-methylenebisacrylamide crosslinking agent and 5mL of distilled water to the mixture obtained in step (2) for dilution; (4) Dissolve 0.03g of ammonium persulfate initiator in 5mL of distilled water, add it to the reaction system obtained in step (3), and continue stirring at 75℃ for 10 minutes to initiate graft copolymerization and crosslinking reaction; (5) After the reaction is completed, the gel is placed in a water bath at 75°C for 10 minutes to form a uniform gel. The gel is then poured into anhydrous ethanol and soaked for 2 minutes. After pouring out the ethanol, fresh anhydrous ethanol is added and the gel is soaked for another 24 hours to complete the dehydration. The dehydrated gel is then dried in an oven at 50°C for 24 hours to obtain cassava starch grafted acrylamide hydrogel.
[0037] Example 2 This embodiment is based on the above embodiment 1. The similarities with embodiment 1 will not be repeated. The difference between this embodiment and embodiment 1 is that the gelatinization temperature in step (1) is 70°C and the gelatinization time is 35 minutes.
[0038] Example 3 This embodiment is based on the above embodiment 1. The similarities with embodiment 1 will not be repeated. The difference between this embodiment and embodiment 1 is that the stirring temperature in step (2) is 80°C and the stirring time is 15 minutes.
[0039] Example 4 This embodiment is based on the above embodiment 1. The similarities with embodiment 1 will not be repeated. The difference between this embodiment and embodiment 1 is that the stirring temperature in step (4) is 70°C and the stirring time is 12 minutes.
[0040] Example 5 This embodiment is based on the above embodiment 1. The similarities with embodiment 1 will not be repeated. The difference between this embodiment and embodiment 1 is that the drying temperature in step (5) is 45°C and the drying time is 26 hours.
[0041] Example 6 This embodiment is based on the above embodiment 1. The similarities with embodiment 1 will not be repeated. The differences between this embodiment and embodiment 1 are as follows: the gelatinization temperature in step (1) is 75°C and the gelatinization time is 30 minutes; the stirring temperature in step (2) is 75°C and the stirring time is 20 minutes; the stirring temperature in step (4) is 75°C and the stirring time is 10 minutes; and the drying temperature in step (5) is 50°C and the drying time is 24 hours.
[0042] Comparative Example 1 This comparative example is based on the above Example 1. The similarities with Example 1 will not be repeated. The difference between this comparative example and Example 1 is that: no acrylamide monomer is added in step (2), that is, the cassava starch is directly cross-linked after gelatinization to prepare pure starch gel.
[0043] Comparative Example 2 This comparative example is based on Example 1 above. The similarities with Example 1 will not be repeated. The difference between this comparative example and Example 1 is that 3g of acrylamide monomer (i.e., the mass ratio of starch to acrylamide is 1:3) is added in step (2).
[0044] Comparative Example 3 This comparative example is based on the above Example 1. The similarities with Example 1 will not be repeated. The difference between this comparative example and Example 1 is that 7g of acrylamide monomer (i.e., the mass ratio of starch to acrylamide is 1:7) is added in step (2).
[0045] Comparative Example 4 This comparative example is based on the above Example 1. The similarities with Example 1 will not be repeated. The difference between this comparative example and Example 1 is that 0.12g of N,N-methylenebisacrylamide crosslinking agent is added in step (3).
[0046] Comparative Example 5 This comparative example is based on the above Example 1. The similarities with Example 1 will not be repeated. The difference between this comparative example and Example 1 is that 0.06g of ammonium persulfate initiator is added in step (4).
[0047] The hydrogels prepared in the above embodiments and comparative examples were subjected to the following performance tests: (1) Determination of swelling equilibrium ratio (SR): Weigh 1g of dry hydrogel sample, immerse it completely in 400mL of distilled water, swell to equilibrium at room temperature, remove it, dry the surface moisture and weigh it, and calculate the swelling equilibrium ratio according to the following formula: SR (%) = (W-W0) / W0×100%, where W0 and W are the masses of hydrogel before and after swelling, respectively.
[0048] (2) Tensile property test: The hydrogel after swelling equilibrium is cut into standard dumbbell-shaped strips, and tensile test is performed using a universal testing machine. The tensile ratio at which the sample breaks is recorded.
[0049] (3) Temperature sensitivity test: The hydrogel sample was placed in distilled water at 25℃, 35℃, 45℃, 55℃, 65℃ and 75℃ respectively to swell to equilibrium. The swelling equilibrium ratio at each temperature was measured. The standard for determining the validity of temperature sensitivity was that the swelling ratio reached its maximum value at 35℃.
[0050] (4) pH sensitivity test: The hydrogel samples were placed in distilled water with pH=2.68, 6.8, 7.2 and 12.5 respectively to swell until equilibrium, and the swelling equilibrium ratio under each pH condition was measured. The standard for determining pH sensitivity was that the swelling ratio under alkaline conditions was higher than that under acidic conditions.
[0051] The results of the hydrogel performance test are shown in Table 1.
[0052] Table 1
[0053] Table 1 shows that the swelling equilibrium ratios of Examples 1 to 6 are all above 600%, with Example 1 reaching the highest at 650%, indicating that the hydrogel prepared by this invention has excellent water absorption capacity. The stretching ratios of all examples are more than 5 times the original length (5.0 to 5.2 times), demonstrating good mechanical strength. Regarding temperature sensitivity, all examples show that the swelling equilibrium ratio reaches its maximum value at 35°C, confirming the existence of temperature sensitivity. Regarding pH sensitivity, all examples show that the swelling ratio is higher under alkaline conditions than under acidic conditions, confirming the existence of pH sensitivity.
[0054] Comparative Example 1 is a pure starch gel without the addition of acrylamide monomer. Its swelling equilibrium ratio is only 180%, its stretching ratio is only 0.8 times, and it does not have temperature sensitivity or pH sensitivity. This indicates that acrylamide grafting is indispensable for improving the performance of hydrogels. Without acrylamide grafting, it is impossible to form a three-dimensional network structure with sufficient crosslinking density and hydrophilicity, and it is also impossible to obtain dual-sensitive response characteristics.
[0055] The swelling equilibrium ratios of Comparative Example 2 (acrylamide dosage of 3g) and Comparative Example 3 (acrylamide dosage of 7g) were 420% and 385%, respectively, with stretch ratios of 3.5 times and 3.8 times, both lower than that of Example 1 (650%, 5.2 times), and neither exhibited temperature sensitivity or pH sensitivity. These results indicate that insufficient acrylamide dosage results in insufficient grafting density, preventing the formation of an effective three-dimensional network structure; excessive acrylamide dosage leads to overly dense crosslinking points, reducing free space and causing a decrease in swelling performance. Furthermore, excessively high grafting density disrupts the hydrophilic / hydrophobic balance in the network structure, resulting in the loss of dual-sensitivity properties. Only when the starch-to-acrylamide mass ratio is 1:5, with the grafting density falling within the critical range, can high swelling capacity, high mechanical strength, and dual sensitivity be simultaneously achieved.
[0056] The swelling equilibrium ratios of Comparative Example 4 (0.12 g of crosslinking agent) and Comparative Example 5 (0.06 g of initiator) were 350% and 410%, respectively, with stretching ratios of 4.2 times and 3.6 times, both lower than that of Example 1, and neither exhibited temperature sensitivity or pH sensitivity. Doubling the amount of crosslinking agent led to increased crosslinking density, more crosslinking points, smaller crosslinking spacing, and an overly dense network structure with reduced free space, making it difficult for water molecules to enter. This significantly reduced swelling performance, and the excessively high crosslinking density fixed the polymer chain segments, preventing them from responding to changes in volume with external temperature and pH, resulting in the loss of dual sensitivity. Doubling the amount of initiator resulted in shorter and more numerous molecular chains, also leading to increased crosslinking density, making it difficult for water molecules to enter the gel interior. It may also trigger free radical degradation reactions, further disrupting the regularity of the network structure and causing the loss of dual sensitivity.
[0057] The above results indicate that the hydrogel exhibits optimal swelling equilibrium ratio, mechanical strength, and temperature / pH sensitivity only when acrylamide is used as the sole grafting monomer, the mass ratio of cassava starch to acrylamide is 1:5, the amount of N,N-methylenebisacrylamide is 0.06 parts by mass, and the amount of ammonium persulfate is 0.03 parts by mass. The crosslinking network formed by the single acrylamide grafting system at a specific critical ratio falls precisely within the critical range of hydrophilic / hydrophobic equilibrium. When the grafting density, crosslinking density, and initiation efficiency are all optimally matched, the polymer chain segments possess sufficient mobility to respond to changes in external temperature and pH, and also have sufficient crosslinking strength to resist external force damage, thus simultaneously achieving a synergistic unity of high swelling capacity, high mechanical properties, and dual sensitivity. Changing any of the above key ratios will destroy the aforementioned synergistic effect, further verifying the inventiveness and irreplaceability of the technical solution of this invention.
[0058] In summary, this invention uses cassava starch as raw material and acrylamide as a single grafting monomer to prepare a cassava starch-grafted acrylamide hydrogel with dual temperature and pH sensitivity through free radical graft copolymerization and crosslinking reactions. Compared with the existing acrylic acid and acrylamide binary copolymer system, this invention uses a single acrylamide grafting system. Under a specific ratio (cassava starch:acrylamide = 1:5, 0.06 parts crosslinking agent, 0.03 parts initiator), the crosslinking network formed falls precisely within the critical range of hydrophilic / hydrophobic equilibrium, resulting in a swelling equilibrium ratio of over 600% and the ability to stretch to more than 5 times its original length without breaking after swelling. It also exhibits excellent mechanical properties and dual sensitivity characteristics. This hydrogel achieves a curcumin loading of 100 mg / g and a cumulative release rate of 80% after 72 hours, while pure curcumin is completely released after 8 hours, extending the sustained-release time by approximately 9 times. Regarding Cu... 2+ The adsorption conforms to the pseudo-second-order kinetic model and the Freundlich isothermal adsorption model, and thermodynamic parameters confirm that the adsorption is a spontaneous endothermic process. The preparation process of this invention is simple, the conditions are mild, and it is easy to scale up for production, showing broad application prospects in the fields of drug sustained-release carriers and heavy metal wastewater treatment.
[0059] The embodiments described above are merely illustrative of more specific and detailed implementations of the present invention, and should not be construed as limiting the scope of the invention. It should be noted that those skilled in the art can make various modifications and improvements without departing from the concept of the present invention, and these all fall within the scope of protection of the present invention. Therefore, the scope of protection of the present invention should be determined by the appended claims.
Claims
1. A cassava starch-grafted acrylamide hydrogel, characterized in that, The hydrogel uses acrylamide as the sole graft monomer, forming a three-dimensional network structure through N,N-methylenebisacrylamide crosslinking between the cassava starch backbone and acrylamide grafted side chains. The hydrogel exhibits both temperature and pH sensitivity, reaching its maximum swelling equilibrium ratio at 35°C, and its swelling performance is higher under alkaline conditions than under acidic conditions. The swelling equilibrium ratio of the hydrogel is over 600%. After swelling equilibrium, the hydrogel can be stretched to more than five times its original length without breaking, rapidly rebounds to its original shape after compression, and remains intact when knotted. The infrared spectrum of the hydrogel is at 1678 cm⁻¹. -1 The hydrogel exhibits a characteristic absorption peak of CN amide and has a three-dimensional interconnected porous structure with a relative crystallinity of 18.32%.
2. The hydrogel according to claim 1, characterized in that, The hydrogel reaches swelling equilibrium in distilled water after 3 hours.
3. The hydrogel according to claim 1, characterized in that, The hydrogel has a curcumin loading capacity of 100 mg / g. The curcumin-loaded hydrogel is released at 37°C in phosphate buffer at pH 7.4, with a cumulative release rate of 80% after 72 hours.
4. The hydrogel according to claim 1, characterized in that, The hydrogel is effective against Cu 2+ The equilibrium adsorption capacity is 10.39~18.39 mg / g.
5. A method for preparing cassava starch grafted acrylamide hydrogel as described in any one of claims 1-4, characterized in that, Includes the following steps: (1) Add 1 part by weight of cassava starch to 100 parts by weight of distilled water, heat and stir in a water bath at 70~80℃ for 25~35 minutes to completely gelatinize the cassava starch and obtain starch gelatinized liquid; (2) Add 5 parts by weight of acrylamide monomer to the starch gelatinization liquid and stir at 70~80℃ for 15~25 minutes to make the acrylamide monomer and gelatinized starch evenly mixed; (3) Add 0.06 parts by weight of N,N-methylenebisacrylamide crosslinking agent and 5 parts by weight of distilled water to the mixture obtained in step (2) for dilution; (4) Dissolve 0.03 parts by weight of ammonium persulfate initiator in 5 parts by weight of distilled water, add it to the reaction system obtained in step (3), and continue stirring at 70~80℃ for 8~12 minutes to initiate graft copolymerization and crosslinking reaction; (5) After the reaction is completed, the gel is placed in a water bath at 70-80°C for 8-15 minutes to form a uniform gel. The gel is then poured into anhydrous ethanol and soaked for 1-3 minutes. After pouring out the ethanol, fresh anhydrous ethanol is added and the gel is soaked for 22-26 hours to complete the dehydration. The dehydrated gel is then dried in an oven at 45-55°C for 22-26 hours to obtain the cassava starch grafted acrylamide hydrogel as described in claim 1.
6. The preparation method according to claim 5, characterized in that, The gelatinization temperature in step (1) is 75°C and the gelatinization time is 30 minutes; the stirring temperature in step (2) is 75°C and the stirring time is 20 minutes; the stirring temperature in step (4) is 75°C and the stirring time is 10 minutes.
7. The preparation method according to claim 5, characterized in that, The drying temperature in step (5) is 50°C, the drying time is 24 hours, and the anhydrous ethanol soaking time is 2 minutes and 24 hours.
8. The application of the cassava starch-grafted acrylamide hydrogel according to any one of claims 1-4 as a sustained-release carrier for curcumin, characterized in that, The hydrogel was loaded with curcumin using an adsorption-based drug loading method. The loading conditions were: adsorption time of 0.5 hours, ethanol concentration of 20%, temperature of 35°C, and initial curcumin concentration of 100 μg / mL. The hydrogel could load 100 mg / g of curcumin. The curcumin-loaded hydrogel was released at 37°C in phosphate buffer solution at pH 7.4, with a cumulative release rate of 80% over 72 hours. The curcumin release process was divided into a burst release phase of 0–2 hours, a slow release phase of 2–48 hours, and a balanced sustained release phase of 48–72 hours. The comparative pure curcumin was completely released within 8 hours under the same conditions, with a release rate of over 99%.
9. The cassava starch-grafted acrylamide hydrogel according to any one of claims 1-4 as a heavy metal Cu 2+ The application of adsorbent materials is characterized by, The adsorption conditions are: per 50 mL Cu 2+ The solution used 2.5 g of the hydrogel, the solution pH was neutral, the temperature was 35°C, and Cu... 2+ The initial concentration was 50 mg / L, and the adsorption time was 24 hours; the hydrogel was effective against Cu. 2+ The adsorption process conforms to a pseudo-second-order kinetic model, with a correlation coefficient R. 2 >0.999; the adsorption process conforms to the Freundlich isothermal adsorption model, with 1 / n values between 0.268 and 0.429; the adsorption thermodynamic parameters are ∆G<0, ∆H=18.926kJ / mol, and ∆S=73.627J / (mol·K), and the adsorption is a spontaneous endothermic process.
Citation Information
Patent Citations
Preparation technology of hydrogel for urea controlled release carrier
CN105693931A
Cassava starch hydrogel nostoc commune extract mask matrix and preparation method thereof
CN105769748A